Theory and Practice in the Bioarchaeology of Care - Tilley, Lorna (Springer, 2020)
This book provides the first comprehensive introduction to, and explanation of, the theory and practice of the 'bioarchaeology of care', an original, fully theorised and contextualised case study-based approach designed to identify and interpret cases of care provision in prehistory.